How does COVID-19 fear affect job insecurity and stress for hospitality employees? A moderated mediation model for age and financial status - Engin Üngüren; Serdar Arslan (Tourism & Management Studies)
This study aims to understand the integrated effect of COVID-19 fear, age, financial situation, and job insecurity on the perceived stress of employees of five-star hotels during the COVID-19 pandemic by proposing a moderated mediation model. A survey was administered to 631 hotel employees working in 22 different five-star hotels in Alanya, Turkey. Moderator, mediation, and moderated mediation relationships were tested with the SPSS macro PROCESS. It was found that COVID-19 fear has both direct and interactive effects on stress and job insecurity, and the indirect effect of COVID-19 fear on stress through job insecurity varies according to the age of the employees and their financial status. The results, which contribute to a better understanding of the effects of COVID-19 on hospitality employees, point out the importance of financial support (organisational and governmental) and transparent communication between the management and employees in times of crisis, such as the COVID-19 pandemic. It is also suggested that hotels should review their unpaid leave policies. The limitations of the study are discussed at the end.